1993
DOI: 10.1007/bf00157395
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak of severe Pseudomonas aeruginosa infections in haematological patients

Abstract: From June to September 1988, an outbreak of Pseudomonas aeruginosa infections in neutropenic patients admitted to the Haematological Wards of "Ospedali Riuniti" in Bergamo, Italy, was detected. Out of 11 cases of P. aeruginosa infections, 8 were bacteremic. Of these, 7 died within few days of onset (mortality rate: 87.5%). Consequently, possible sources of infection were investigated, and moist areas of the hospital environment were shown to be highly contaminated by P. aeruginosa. A clinical and microbiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The presence of outbreak strains in tap water, not including only P. aeruginosa but also other microorganisms, seem to be an important factor in subsequent dispersion and potential disease transmission within a healthcare setting [8]. Regular disinfection of contaminated water lines, water fittings, and change of water aerators in critical areas can reduce the number of colony-forming units and was shown to reduce the number of healthcare associated infections due to water-borne pathogens [9].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of outbreak strains in tap water, not including only P. aeruginosa but also other microorganisms, seem to be an important factor in subsequent dispersion and potential disease transmission within a healthcare setting [8]. Regular disinfection of contaminated water lines, water fittings, and change of water aerators in critical areas can reduce the number of colony-forming units and was shown to reduce the number of healthcare associated infections due to water-borne pathogens [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis, only those studies in which the outbreak had been confirmed by genotyping of the Pseudomonas isolates were included (Tables 1-5). We then decided to include three additional publications: the first one from 1989 used antimicrobial sensitivity testing, and plasmid analysis [2]; the second one from 1993 used serotyping, pigment production, lysotyping, and antibiotic susceptibility testing [20], and the last one from 2006 described the nosocomial spread of pandrug-resistant P. aeruginosa sensitive only to colistin [21]. No typing of the isolates was performed for the latter study.…”
Section: Methodsmentioning
confidence: 99%
“…Although inoculation of blood culture bottles subsequently to that of the blood-gas machine was not a practice in the NICU, a new member of the staff had unwittingly performed this procedure (2 pseudoinfections). Grigis et al 1993 [20] Sanitary [31] Colonized/infected patients appeared to be the major source of cross-contamination. Patient-to-patient transmission via physicians / HCWs Contaminated antiseptic?…”
Section: Confirmation Of An Outbreak By Typing Of the Isolatesmentioning
confidence: 99%
“…It is often found in moist environment and can cause infections in immunocompromised or otherwise susceptible hosts [1,2]. Numerous outbreaks have been associated with faulty or unclean medical equipment or products [3-9], contaminations from personnel or environmental reservoirs [10-16]. Cross-colonization and cross-contamination within hospitals has been documented [13,17,18].…”
Section: Introductionmentioning
confidence: 99%